1999
DOI: 10.1159/000026066
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function and Severity of Mitral Stenosis

Abstract: Objective: To correlate the degree of severity in patients with rheumatic mitral stenosis to pulmonary function data and to their respiratory symptoms. Methods: Pulmonary function and the MCR questionnaire on respiratory symptoms were made in 43 patients with simple mitral stenosis (SMS), and 79 patients with advanced mitral stenosis scheduled for valve replacement surgery (MVR). Results: All the patients in the two groups had restrictive and obstructive patterns. They had reduced forced vital capacity (FVC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It is suggested that the increase in distribution of cardiac output after PTMC to respiratory muscle might change the force of diaphragm and other respiratory muscle causing increase in value of FEV 1 and FVC. 4 In a study, post procedural pulmonary function tests revealed significant improvement of FVC and TLC, i.e. disappearance of restrictive pattern on long term follow up.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It is suggested that the increase in distribution of cardiac output after PTMC to respiratory muscle might change the force of diaphragm and other respiratory muscle causing increase in value of FEV 1 and FVC. 4 In a study, post procedural pulmonary function tests revealed significant improvement of FVC and TLC, i.e. disappearance of restrictive pattern on long term follow up.…”
Section: Discussionmentioning
confidence: 95%
“…Hypertrophied and hyperplastic airway smooth muscle and increased wall thickness are also heightened along with bronchial hyper-reactivity. 4 Thus, the effect is completely mechanical one and depends on the degree of stenosis of mitral valve. The major act of affray comes into account from several studies are reduction in pulmonary compliance ventilation-perfusion mismatch, reduction in diffusion capacity, increased "pulmonary capillary blood volume" and hyperventilation in exercise in relation to the oxygen uptake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The deterioration in lung function in mitral stenosis correlates with the severity of stenotic valves and the severity of respiratory symptoms. 6 A correlation is noted between vital capacity (VC) and the severity of dyspnoea in patients with mitral stenosis. It was reported that the degree of dyspnoea showed a closer relation to the height of pulmonary artery pressure and to VC, than to maximum breathing capacity in the pure mitral stenosis patients.…”
mentioning
confidence: 99%